EXPLORING THE VALUES OF LOCAL WISDOM OF THE COMMUNITY AS A SOURCE OF SOCIAL SCIENCE LEARNING: MENGGALI NILAI-NILAI KEARIFAN LOKAL MASYARAKAT SEBAGAI SUMBER BELAJAR ILMU PENGETAHUAN SOSIAL - Kendedes Tambunan; Sudrajat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study is grounded in the importance of integrating local wisdom values into Social Studies (IPS) learning to create contextual, relevant, and character-oriented education. Conventional Social Studies instruction in Indonesia often remains theoretical and detached from students’ social and cultural realities. Therefore, this research aims to identify the values of local wisdom embedded in Indonesian communities that are relevant to Social Studies learning and to analyze how these values can be effectively implemented in classroom practices. This study employs a qualitative approach using a literature review method. Data were collected from scientific articles, books, research reports, and educational policy documents related to local wisdom and Social Studies education. The data collection technique involved documentation, while data analysis consisted of reduction, presentation, and conclusion drawing to synthesize key findings across sources. The results indicate that local wisdom values such as mutual cooperation (gotong royong), deliberation (musyawarah), honesty, and social concern are highly relevant to the objectives of Social Studies education. These values can be incorporated into learning through ethnopedagogical, contextual, and project-based approaches to enhance students’ social awareness, responsibility, and cultural identity. The study concludes that integrating local wisdom into Social Studies learning not only strengthens students’ character development but also contributes to cultural preservation and sustainable community development.